Multinationals, the State and Control of the Nigerian Economy - Biersteker, Thomas J. (Book collections on Project MUSE., 2014)
Thomas Biersteker evaluates the sources of Third World economic nationalism and assesses the significance of the changes that have taken place between North and South since the early 1970s. Neo-classical and neo-Marxist approaches to international and comparative political economy are explored to develop methods and select criteria for the assessment of major change. Originally published in 1987. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton Univers.